2010
DOI: 10.1063/1.3380592
|View full text |Cite
|
Sign up to set email alerts
|

Properties of nitrogen implanted and electron beam annealed bulk ZnO

Abstract: The optical properties of bulk ZnO ion implanted with nitrogen ions, at an energy of 23 keV have been studied as a function of implantation fluence and electron beam (EB) annealing conditions. Nuclear reaction analysis and Raman results have revealed the implanted N concentration and its structural changes with respect to various nitrogen ion fluences. The optical properties of nitrogen implanted bulk ZnO were investigated by low temperature photoluminescence measurements. An enhanced peak at 3.235 eV has been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(30 citation statements)
references
References 28 publications
1
29
0
Order By: Relevance
“…3. These lines have been previously observed 8,12,40,41 in N-doped ZnO and were attributed to nophonon and LO-assisted radiative transitions which involve a deep N acceptor. The exact origin of the responsible recombination process remains, however, highly controversial as the emission has been assigned to recombination of excitons bound to a neutral acceptor (A 0 X) 8,42 and also to free electron to acceptor (FA) transitions.…”
Section: B Photoluminescencementioning
confidence: 90%
“…3. These lines have been previously observed 8,12,40,41 in N-doped ZnO and were attributed to nophonon and LO-assisted radiative transitions which involve a deep N acceptor. The exact origin of the responsible recombination process remains, however, highly controversial as the emission has been assigned to recombination of excitons bound to a neutral acceptor (A 0 X) 8,42 and also to free electron to acceptor (FA) transitions.…”
Section: B Photoluminescencementioning
confidence: 90%
“…This pre-treatment of annealing is carried out to ensure that the steel samples are defect-free initially. Two sets of such solution annealed samples have been implanted at room temperature with 30 keV N 15 ions to a fluence of 1 Â 10 15 and 5 Â 10 15 atoms cm À2 using the GNS dual low-energy ion implantation facility [12]. The ion beam has been raster scanned over the surface to produce a laterally homogeneous implantation into substrate.…”
Section: Methodsmentioning
confidence: 99%
“…It was found that the few of the phonon modes cannot be assigned to the host ZnO and C: ZnO film which suggests the presence of an additional phonon mode (APM). The similar kind of APM in RS was reported undoped and Cdoped ZnO thin-films prepared by various physical and chemical methods [1,12].…”
Section: Micro-raman Spectroscopy Analysismentioning
confidence: 99%